The Best Available Evidence: Assessing the Quality of Nursing Students’ Bibliographies - Brown, David; Hewitt, Ted; Nannen, Devi; Powell, Jessica; Savage Grainge, Anita (Journal of Academic Writing, 2018)
Librarians and academic staff suggest a relationship between the quality of references which students use in academic assignments and the marks received. This study tested that assertion by using a citation analysis methodology to assess the quality of bibliographies written by undergraduate nursing students at the University of York. Bibliographies from sixty essays across three modules were analysed, noting the types and quantities of references used and whether references were sourced independently or included in the module’s reading list. Each bibliography was given an overall quality rating: ‘Poor’, ‘Average’ or ‘Good’. This rating was compared with the mark the student was awarded for the essay. Results showed that, whilst students demonstrated the ability to locate items independently, the quality of those items was often poor. Generally, quality of selected sources and bibliographies improved as students progressed through the programme. There was an association between higher quality bibliographies and higher assignment marks. The study concludes that critical thinking skills are vital for nursing students to develop academically, as these skills will be tested within a clinical environment once students have completed their degree. A benefit for students is the conclusion that using higher quality sources results in higher marks.